Pemanfaatan Lingkungan Sekitar Sebagai Sumber Belajar IPS di SD/MI - Harahap, Sania Mar’i Adnanda; Yana, Suci Pitri; Nurmadayanti, Nurmadayanti; Nasution, Laila Khairani; Hutabarat, Satria; Yusnaldi, Eka (Education Achievement: Journal of Science and Research, 2025)
Social Sciences (IPS) learning in SD/MI has an important role in building students' understanding of social, national and state life. One effective approach in learning social studies is to utilize the surrounding environment as a learning resource. This article aims to examine the use of the surrounding environment as a medium for social studies learning in SD/MI through literature studies. The surrounding environment, whether physical, social or cultural, has great potential to increase the relevance and activeness of learning. Utilization of the environment can be done through direct observation, case studies, or simulated situations that reflect students' daily lives. The results of the study show that using the surrounding environment as a learning resource can increase student motivation, develop critical thinking skills, and enrich contextual learning experiences. However, its use requires careful planning by teachers, including the preparation of appropriate evaluation methods and instruments. Thus, the integration of the environment as a social studies learning resource is able to create more meaningful, relevant and contextual learning for elementary/MI students.